Endogenous target mimics down-regulate miR160 mediation of ARF10, -16, and -17 cleavage during somatic embryogenesis in Dimocarpus longan Lour - Lin, Yuling; Lai, Zhongxiong; Tian, Qilin; Lin, Lixia; Lai, Ruilian; Yang, Manman; Zhang, Dongmin; Chen, Yukun; Zhang, Zihao (Frontiers in Plant Science, 2015)
MicroRNA160 plays a critical role in plant development by negatively regulating the auxin response factors ARF10, -16 and -17. However, the ways in which miR160 expression is regulated at the transcriptional level, and how miR160 interacts with its targets during plant embryo development, remain unknown. Here, we studied the regulatory relationships among endogenous target mimics (eTMs), and miR160 and its targets, and their involvement in hormone signaling and somatic embryogenesis (SE) in Dimocarpus longan. We identified miR160 family members and isolated the miR160 precursor, primary transcript, and promoter. The promoter contained cis-acting elements responsive to stimuli such as light, abscisic acid, salicylic acid and heat stress. The pri-miR160 was down-regulated in response to salicylic acid but up-regulated by gibberellic acid, ethylene, and methyl jasmonate treatment, suggesting that pri-miR160 was associated with hormone transduction. Dlo-miR160a, -a* and -d* reached expression peaks in torpedo-shaped embryos, globular embryos and cotyledonary embryos, respectively, but were barely detectable in embryogenic callus. This suggests that they have expression-related and functional diversity, especially during the middle and later developmental stages of SE. Four potential eTMs for miR160 were identified. Two of them, glucan endo-1,3-beta- glucosidase-like protein 2-like and calpain-type cysteine protease DEK1, were confirmed to control the corresponding dlo-miR160a* expression level. This suggests that they may function to abolish the binding between dlo-miR160a* and its targets. These two eTMs also participated in auxin and ABA signal transduction. DlARF10, -16, and -17 targeting by dlo-miR160a was confirmed; their expression levels were higher in friable-embryogenic callus and incomplete compact pro-embryogenic cultures and responded to 2,4-D, suggesting they may play a major role in the early stages of longan SE dependent on 2,4-D. The eTMs, miR160, and ARF10, -16 and -17 exhibited tissue specificity in ‘Sijimi’ longan vegetative and reproductive organs, but were not negatively correlated. These results provide insights into the possible role of the eTM-miR160-ARF10-16-17 pathway in longan somatic embryo development.